Cover Feature: General Synthesis of Transition‐Metal Oxide Hollow Nanospheres/Nitrogen‐Doped Graphene Hybrids by Metal–Ammine Complex Chemistry for High‐Performance Lithium‐Ion Batteries (Chem. Eur. J. 9/2018). Issue 9 (30th November 2017) - Chen, Jiayuan; Wu, Xiaofeng; Gong, Yan; Wang, Pengfei; Li, Wenhui; Mo, Shengpeng; Peng, Shengpan; Tan, Qiangqiang; Chen, Yunfa
Abstract : A general and facile strategy based on metal–ammine complex chemistry has been developed to synthesize a series of hollow transition‐metal oxides (TMOs)/nitrogen‐doped graphene (NG) hybrids, applied as anodic materials in high‐performance lithium‐ion batteries. The porosity of hollow TMOs coupling with porous NG frameworks produce shorter diffusion paths of Li + and electrolyte, smaller volume changes of electrodes and higher electron conductivity during long‐time charge/discharge process. More information can be found in the Full Paper by X. Wu, Y. Chen et al. onpage 2126 .